Inside Chanakyas Mind : Aanvikshiki and the Art of Thinking - Radhakrishnan Pillai (Portfolio /Penguin Random House India, 2017)
Chanakya was one of the best strategic thinkers of the world. In the fourth century BC, he wrote the Arthashastra, an unrivalled political treatise that has since been used by leaders across the globe. In Inside Chanakyas Mind, for the first time, Radhakrishnan Pillai, the bestselling author of Corporate Chanakya, will distill Chanakyas age-old wisdom on how to think to the masses through his practical and innovative approach.